Structure and Conformation of Novel BODIPY Ugi Adducts - Dr. Ismael Javier Arroyo‐Córdoba; Gonzalo Gamboa‐Velázquez; Dr. Claudia Gabriela Avila‐Ortiz; Marco A. Leyva‐Ramírez; María Teresa Cortez‐Picasso; Prof. Dr. Marco A. García‐Revilla; Diana E. Ramírez‐Ornelas; Prof. Dr. Eduardo Peña‐Cabrera; Prof. Dr. Eusebio Juaristi (ChemistryOpen, 2022)
Abstract Two novel BODIPY‐Ugi (boron dipyrromethene) adducts exhibit peculiar room temperature (T=20 °C) H‐1 NMR spectra in that several protons located at the aromatic aniline‐type ring are lost in the baseline. This observation revealed the existence of a dynamic conformational process where rotation around the C−N bond is hindered. Variable‐temperature H‐1 and C‐13 NMR spectroscopic analysis confirmed this conclusion; that is, low‐temperature spectra show distinct signals for all four aromatic protons below coalescence, whereas average signals are recorded above coalescence (T=+120 °C). Particularly interesting was the rather large difference in chemical shifts for the ortho protons below coalescence, Δδ=1.45 ppm, which was explained based on DFT computational analysis. Indeed, the calculated lowest‐energy gas‐phase conformation of the BODIPY Ugi adducts locates one half of the aniline‐type ring in the shielding anisotropic cone of the bridge phenyl ring in the BODIPY segment. This is in contrast to the solid‐state conformation established by X‐ray diffraction analysis that shows a nearly parallel arrangement of the aromatic rings, probably induced by crystal packing forces.